Detection the Level of Anxiety and Depression among Diabetic Foot Patients at Al-Najaf Al-Ashraf Teching Hospitals (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: The study was done to assess the level of anxiety and depression among diabetic foot patientsat Al-Najaf Al-Ashraf Teaching Hospitals. Also to find out relationships between anxiety and depressionof diabetic foot patients and their demographic characteristics. Methodology: a descriptive correlationaldesign, the study established for a period from 10th October, 2020 to 1st June, 2021. The study was conductedon a probability (accidental) sample of 120 patients who have a diabetic foot which was selected from Al-Sadder teaching hospital and Al-Furat teaching hospital in Al-Najaf Al-Ashraf Governorate. The researcheris using the Hospital Anxiety and Depression Scale to assess the level of anxiety and depression. Results:The result of the study showed (37.5%) of the study sample had moderate anxiety. Furthermore, the studyshows (36.6%) of the study participant have moderate depression. Contingency correlation analysis showedthat anxiety and depression is a significant correlation with the number of hospital admission, duration ofcurrent admission, and previous amputation. In addition, anxiety was significantly correlated with gender,educational level, duration of the diabetic foot. Besides, depression was significantly correlated with age,economic status, having other chronic diseases.